Decreased effectiveness of fiscal and monetary policies in Japan's aging society - Naoyuki Yoshino; Hiroaki Miyamoto (Asian Development Bank Institute (ADBI), 2017)
This paper studies how an aging population affects economic performance and the effectiveness of fiscal and monetary policies. We develop a New Keynesian dynamic stochastic general equilibrium model with heterogeneous households, workers, and retirees. We demonstrate that an increase in the proportion of working population increases aggregate output, consumption, and investment by increasing total labor supply in the long run. It also increases wages and reduces social security burden of the government. This paper also finds that effectiveness of fiscal and monetary policies is weakened when the proportion of retirees becomes larger. This is the reason why recent monetary policies cannot recover the Japanese economy from the prolonged stagnation.
Keywords: E52; E62; J11; 330; Economics; Social development and protection; Japan